Deixis Analysis in Podcast Zach Sang Show YouTube Channel: Selena Gomez Talks Music, Mental Health and Finding Happiness (2020) - Mukhyar, Trya Indah Lestari; Afriana, Afriana (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
Pragmatics explores the relationship between language and the users of language. Deixis concerns with the use of expression within some utterances to refer to some portion that contains the utterance. The objective of this study is to identify the types of deixis in a podcast Zach sang show YouTube channel. This research was used qualitative methods. The data analysis was performed by categorizing data based on the theory from Levinson  (1997) that include person deixis, time deixis, place deixis , discourse deixis and social deixis. There are 1.167 raw data items. However, the researchers analyzed eighteen data based on the types of deixis.  The use of person deixis contained six data, four data contained time deixis, two data contained discourse, and two data contained social deixis for the result of this research. Person deixis is dominant than the other types. Meanwhile, social deixis appeared less frequently because the context is not widely used in that context. This suggests a significant focus on individual references, highlighting the crucial role of personal connections in shaping the podcast’s discourse.